1994
DOI: 10.1016/s0006-3495(94)80674-5
|View full text |Cite
|
Sign up to set email alerts
|

Activity of creatine kinase in a contracting mammalian muscle of uniform fiber type

Abstract: We investigated whether the creatine kinase-catalyzed phosphate exchange between PCr and gamma ATP in vivo equilibrated with cellular substrates and products as predicted by in vitro kinetic properties of the enzyme, or was a function of ATPase activity as predicted by obligatory "creatine phosphate shuttle" concepts. A transient NMR spin-transfer method was developed, tested, and applied to resting and stimulated ex vivo muscle, the soleus, which is a cellularly homogeneous slow-twitch mammalian muscle, to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 52 publications
4
55
0
Order By: Relevance
“…To some extent, it seems possible to reconcile these datasets and views by recognizing that soleus muscles possess much lower mitochondrial volume densities than hearts. The data obtained by McFarland et al (1994) are therefore consistent with Meyer et al (1984), given what is observable using 31 P-NMR in this system. In hearts with greater mitochondrial volume density, CK net fluxes occurring in opposite directions are observable at the mitochondria and the myofibrils, where compartmentalized or channeled reactions occur, while equal and reversible fluxes are also observed in the cytosol (Joubert et al, 2002).…”
Section: Creatine Kinase and Atp Turnover In Aerobic Musclessupporting
confidence: 81%
See 1 more Smart Citation
“…To some extent, it seems possible to reconcile these datasets and views by recognizing that soleus muscles possess much lower mitochondrial volume densities than hearts. The data obtained by McFarland et al (1994) are therefore consistent with Meyer et al (1984), given what is observable using 31 P-NMR in this system. In hearts with greater mitochondrial volume density, CK net fluxes occurring in opposite directions are observable at the mitochondria and the myofibrils, where compartmentalized or channeled reactions occur, while equal and reversible fluxes are also observed in the cytosol (Joubert et al, 2002).…”
Section: Creatine Kinase and Atp Turnover In Aerobic Musclessupporting
confidence: 81%
“…In their insightful analysis, Meyer et al (1984) argued that the transport functions of creatine and CrP are simply consequences of the near-equilibrium nature of the CK reaction. A decade later, McFarland et al (1994) used a spintransfer NMR method to measure forward and reverse CK flux rates in soleus, a slow-twitch, oxidative muscle. It was found that over a tenfold range of ATP turnover rates, forward and reverse flux rates remain equal and the behaviour of CK in vivo is reconcilable with the kinetic properties of the enzyme in vitro.…”
Section: Creatine Kinase and Atp Turnover In Aerobic Musclesmentioning
confidence: 99%
“…The complexity of cell structure and the specific behavior of mito-and MM-bound CK has been underestimated in the field of NMR spectroscopy where the cell had mostly been considered as a unique compartment of CK at equilibrium (20,28). As a consequence of this assumption, the free ADP concentration in vivo is estimated from the total concentrations of ATP, PCr, and Cr and the global CK equilibrium constant.…”
Section: Discussionmentioning
confidence: 99%
“…As already pointed out by Wallimann (19), the understanding of CK function might be greatly limited when considering the cell as a homogenous system where enzymes and metabolites have uniform distributions and concentrations. Although the necessity of considering metabolic compartmentation has been previously questioned in NMR analysis of the skeletal muscle (20), its importance was earlier proposed in the heart (21,22) but hardly experimentally explored. Neglecting the presence of mitochondrial compartments in the NMR analysis indeed results in errors on the determination of CK fluxes (23).…”
mentioning
confidence: 99%
“…An alternative strategy is to add CK-Mit to a tissue that does not normally contain it, such as the liver, to determine whether there is a gain of function effects. Recently, a transgenic mouse model has been produced that expresses active CK-Mit in liver (22). The CK-Mit localizes properly to the intermembrane space of mitochondria and is capable of synthesizing and utilizing PCr.…”
mentioning
confidence: 99%